Review: Precise sarcoma patient-derived orthotopic xenograft (PDOX) mouse models enable identification of novel effective combination therapies with the cyclin-dependent kinase inhibitor palbociclib: A strategy for clinical application - Higuchi, Takashi; Igarashi, Kentaro; Yamamoto, Norio; Hayashi, Katsuhiro; Kimura, Hiroaki; Miwa, Shinji; Bouvet, Michael; Tsuchiya, Hiroyuki; Hoffman, Robert M. (Frontiers in Oncology, 2022)
Introduction: Sarcomas are rare heterogenous malignant tumors that originate and develop in soft-tissue or bone. Effective treatment of sarcomas is still limited to traditional chemotherapy and surgery which are often ineffective for recurrent disease. Cyclin-dependent kinases (CDKs) promote abnormal cell cycling and cell division in many cancers including sarcomas. Therefore, our hypothesis was CDK inhibitors may be useful candidates for sarcoma treatment. Patient-derived orthotopic xenograft (PDOX) mouse models mimic the clinical disease for all major cancer types and have identified effective treatments that hold much clinical promise. The present report reviews sarcoma PDOX models that we have established for their potential to discover effective combination treatments based on CDK inhibitors for recalcitrant sarcoma. Methods: We have previously reported 6 sarcoma PDOX studies evaluating the CDK inhibitor palbociclib on sarcoma, including osteosarcoma, Ewing’s sarcoma, de-differentiated liposarcoma, and peritoneal metastatic leiomyosarcoma. Results: Palbociclib monotherapy significantly inhibited, but not regressed, the PDOX growth of osteosarcoma, Ewing’s sarcoma, de-differentiated liposarcoma, and peritoneal metastatic leiomyosarcoma. A combination of palbociclib and an mTOR inhibitor, everolimus, significantly inhibited, but did not regress, the PDOX growth of osteosarcoma. Combinations of palbociclib with a multikinase-inhibitor, sorafenib, and palbociclib combined with recombinant methioninase were effective and regressed the osteosarcoma and de-differentiated liposarcoma PDOX models, respectively. Conclusions: Effective therapies including novel drug combinations using a CDK inhibitor were identified in PDOX models of the major types of sarcomas. Methionine restriction effected by methioninase, increased the efficacy of the CDK inhibitor palbociclib, thus combination is a promising future strategy for improved sarcoma therapy in the clinic.